ANALISIS KANDUNGAN UNSUR ESENSIAL DAN TOKSIK DALAM TEH DAN AIR SEDUHANNYA DENGAN AKTIVASI NEUTRON - Mulyaningsih, Th. Rina (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Concentration of metal elements K, Ca, Mn, Mg, Fe, Na, Zn, Rb, Br, Cr, Cs, La,Sc and Co from 14 samples of green and black tea with aroma of jasmine, vanilla, rosella flower and tea infusion have been determined by means of neutron activation analysis. The Samples were chosen from the domestic product and were collected from Supermarket in Serpong region. Neutron irradiation of the samples was carried out in the Irradiation Facility of the RSG-GAS reactor at thermal neutron flux in the order of 1013 ncm-2s-1. The working procedures follow the Standard Operating Procedures of FNCA. As of the quality control the reference material of SRM-NIST 1573a Tomato leaves and NIST 1547 Peach leaves.have been applicated. The analysis results show that concentration of the elements variate depending on the sort of tea. Concentration of Ca, K, Mg dan Mn have a rather high value namely > 100 mg/kg. Concentration of Ca and K have values in a range of 1135.36-9123.21 and 1064.41-2473.12 mg/kg as well as Mg of 2725.6-5528.5; and Mn of 95.38-815.48 mg/kg.Concentration of Na, Fe, Co, La, Cr, Br, Sc, Cs, Rb and Zn <100 mg/kg. Most elements in these tea were released into the infusions at defferent percentages in a range of 27.89-68.94% depending on the sort of the tea. There were not detected toxical elements Hg, Cd and As except Cr with low concentration. Therefore tea drink sare adequately good enough as essential elements source and content no toxic elements.